Unveiling host-guest interactions and stability of amine-functionalized silica sorbents for carbon capture - Ogunedo, Briggs M. O.; Wadi, Basil; Manovic, Vasilije; Nabavi, Seyed Ali (Elsevier, 2025)
Despite making significant progress in terms of capture kinetics and capacity, the thermochemical and cyclic instability of silica-based amine functionalized adsorbents present challenges for their practical implementation and economic viability. Accordingly, this work provides a critical review to analyse factors affecting thermal and cyclic stability of functional silica-based sorbents. The first section provides background information and context for the review. The second section focuses on the synthesis routes employed for silica-based amine functionalized adsorbents. The third section delves into the mechanism underlying the thermal and cyclic instability observed in these adsorbents. The fourth section explored the factors that influence the thermal and cyclic stability of silica-based amine functionalized adsorbents. The last section dissects host-guest interaction in silica-based amine functionalized adsorbents. The review concludes by underscoring the importance of further research and development into host-guest interaction studies in amine functionalized adsorbents to optimize performance and address the challenges associated with thermal and cyclic instability, thereby enhancing the practical feasibility of these adsorbents in carbon capture applications.
Keywords: Thermal stability; Cyclic stability; Adsorption; Diffusion; Amine functionalized adsorbents; Impurities; CO2 capture; 3403 Macromolecular and Materials Chemistry; 34 Chemical Sciences; 13 Climate Action; 3405 Organic chemistry; 3406 Physical chemistry